1998
DOI: 10.1007/bf02524423
|View full text |Cite
|
Sign up to set email alerts
|

Technical aspects of mechnomyography recording with piezoelectric contact sensor

Abstract: The piezoelectric contact sensor has been widely utilised in mechanomyography (MMG). The authors aim to clarify the mechanical variables (i.e. acceleration, velocity or displacement) reflected by the MMG signal detected with a piezoelectric contact sensor (PEC), and compare the results with those obtained simultaneously by an accelerometer (ACC). To measure the acceleration-frequency response, a mechanical sinusoidal excitation of 5 to 300 Hz at a constant magnitude of 0.01 G was applied to the two transducers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 20 publications
3
38
1
Order By: Relevance
“…displacement) was also similar to the force waveform (BARRY, 1992). During voluntary contractions, the amplitude spectral density function of the MMG from the piezoelectric contact sensor resembled that of the double integral of the ACC transducer signal (WATAKABE et al, 1998). in the present study, the frequency response of the voluntary MMG from the MIC transducer was similar to that from the double integral of the ACC transducer.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…displacement) was also similar to the force waveform (BARRY, 1992). During voluntary contractions, the amplitude spectral density function of the MMG from the piezoelectric contact sensor resembled that of the double integral of the ACC transducer signal (WATAKABE et al, 1998). in the present study, the frequency response of the voluntary MMG from the MIC transducer was similar to that from the double integral of the ACC transducer.…”
Section: Discussionsupporting
confidence: 73%
“…Various transducers have been used to record the MMG, including accelerometers (LAMMERT et al, 1976;BARRY, 1992;ORIZIO et al, 1996;AKATAKI et al, 1999), piezoelectric contact sensors (BOLTON Correspondence should be addressed to Dr K. Mita; e-marl: mitak@inst-hsc.pref.aichi 1989;BARRY, 1991;ORIZIO et al, 1994), condenser microphones (BOLTON et at., 1989;MATON et at., 1990;STOKES and DALTON, 1991) and laser distance sensors (ORIZIO et al, 1999). it is evident that the MMG signal detected with an accelerometer and laser distance sensor reflects the acceleration and displacement of the skin vibration, respectively, it is suggested that a piezoelectric contact sensor is indicative of displacement of the muscle vibration and that its mechanical behaviour is explained by a seismic system with a heavy mass element (WATAKABE et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue is ordinarily analysed from the changes in RMS (EMG RMS ) and median frequency (EMG MF ) of EMG signal, but according to additional references [5,6,11] a special method called mechanomyography (MMG) can be employed. MMG monitors amyostasia, which are small vibrations of loaded muscles.…”
Section: Physiological Monitoring Experimentsmentioning
confidence: 99%
“…Usually, the aim of combining sensors with sEMG or other sensors is validation, labelling or improving the signal to noise ratio. To date, no consensus has been reached upon the ideal sensor technology to use for MMG recordings (Courteville et al, 1998;Gregori et al, 2003;Watakabe et al, 1998). The literature suggests that accelerometers are more appropriate than condenser microphones due to the effects of background noise.…”
Section: How Can Muscle Fatigue Be Detected ?mentioning
confidence: 99%